ANALISIS PENDAPATAN DAN KELAYAKAN USAHA COKELAT RAPOVIAKA PADA INDUSTRI RAPOVIAKA SIMPLE DI KOTA PALU - Aeni, Nur; Lamusa, Arifuddin (AGROTEKBIS, 2017)
This study aims to determine the feasibility of income and a chocolate on an industrial Rapoviaka Rapoviaka Simple in Palu City. During the months of April to June 2016. The location determination and respondents were intentionally (purposive). The number of respondents as many as three people. Collecting data in this study consisted of primary data and secondary data.Analysis of the data used is the analysis of income. Research shows the revenues and the feasibility of such chocolate products rapoviaka good so far.This matter Shown results showed that the income earned in May 2016 amounted to USD 10,785,707.3 for chocolate Rapoviaka. Rapoviaka chocolate produced each month in accordance with the availability of raw materials and demand consumer feasibility analysis shows that chocolate processed products are eligible for cultivated Rapoviaka indicated by the value of R / C of 2.17 means that every single rupiah expenses incurred Rapoviaka Simple industry will gain acceptance Rp 2.17 .Â Keywords:Feasibility, Income, Rapoviaka Chocolate